Pengaruh Relationship Marketing dan Kepuasan Pelanggan Terhadap Loyalitas Pelanggan Pada Toko BEST Pematangsiantar - Robert Tua Siregar; Sofiyan Sofiyan; Yansen Siahaan; Christine Loist; Olympic Olympic (Strategic: Journal of Management Sciences, 2021)
Objective. The purpose of this study was to determine: To analyze the effect of relationship marketing on customer satisfaction at the Best Pematangsiantar Store. Then the influence of customer satisfaction on customer loyalty at the Best Pematangsiantar Store. Research Methods. The object of research is Pematangsiantar Best Store which is located on Jl. Sutomo No. 63, Kelurahan Dwikora, Kecamatan Siantar Barat, Pematangsiantar, 21118. In this study, all members of the population were used as data sources, namely as the sample of the researcher. Where the research population is the Best Pematangsiantar Store customers with a total of 35 people, who also become the research sample. Results. The results of simple linear regression analysis show that relationship marketing has a positive effect on customer satisfaction and customer satisfaction has a positive effect on customer loyalty. The results of simple linear regression analysis show that relationship marketing has a strong and positive relationship with customer satisfaction, and customer satisfaction has a very strong and positive relationship with customer loyalty.. The results of the hypothesis test state that H0 is rejected, meaning that relationship marketing has a positive and significant effect on customer satisfaction, and customer satisfaction has a positive and significant effect on customer loyalty. Conclusion. Relationship marketing at the Best Pematangsiantar Store in this case has been categorized as good. Even though it has been categorized as good, the leadership should try to improve and also create long-term relationships with customers and also fulfill all the needs according to the wishes of these customers. Customer satisfaction at the Best Pematangsiantar Store in this case has been categorized as good. Even though it has been categorized as good, it is better for the leadership to maintain long-term relationships and give good attention so that customers will feel more satisfied. Customer loyalty at the Best Pematangsiantar Store in this case has been categorized as good. Even though it has been categorized as good, the leadership should try to establish close relationships with customers and pay attention so that customers become loyal.